Using Geodetic Strategies of Romanticists by Ilia Chavchavadze - Hayate Sotome, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2018)
The discussion on this paper concerns with geopoetic strategy in Ilia Chavchavadze’s travelogue “Letters of a Traveler.” He cites some strophes from Georgian romanticist G. Orbeliani’s poems in the travelogue. According to a previous study, there are three types of geopoetic strategy in Georgian romanticism literature, that indicates different attitudes toward Russian colonialism. Considering these geopoetic strategies, it can be said that the writer notices the differences and use them in order to express his own geopoetic standpoint. Concretely, he cites Orbeliani’s verse “Night of Farewell” ironically because it can be classified into the first type of the strategies which implies Georgian romanticists’ complicity with Russian colonialism in North Caucasus. On the other hand, he cites Orbeliani’s poem “Toast” without any ironic intention because the poem applauses the history of Georgia. Therefore, it can be said that Chavchavadze strategically recreates the national consciousness of the romanticists and use it as inspiration for his own works and actions.